Análisis de tiempo para mejorar los procesos de gestión proyectos I+D+I de la Escuela Superior Politécnica Agropecuaria de Manabí MFL. - Delgado Palacios, Kassandra Rocío (2018)
The study of approximate times to the R + D + i project management processes of the Escuela Superior PolitécnicaAgropecuaria de Manabí “Manuel Félix López”, aimed at improving the established procedures. To do this, the interview technique was used, which allowed gathering information on the subprocesses, activities and tasks, being necessary also the use of the inductive and deductive method, helping to discern the inputs, outputs and areas involved in the process cards to later translate into a flow diagram. Consecutively, through the expert method, the approximate optimal, pessimistic and most probable times were taken, then, an EXCEL matrix was designed to insert the estimated times, and from that information calculate the arithmetic average of each of the activities, to respectivelyapply the formula of estimated times. Then with the analytical - synthetic method, it was possible to analyze and specify the factors immersed in the setbacks, and based on this, an improvement plan was designed in which the strategies to be followed are specified, cause of the problems, purposes or objectives to achieve for optimization in terms of efficiency and effectiveness.